Suicide among those who use mental health services: Suicide risk factors as evidenced from contact-based characteristics in Victoria - Fernando, Tharanga; Clapperton, Angela; Spittal, Matthew; Berecki-Gisolf, Janneke (Frontiers in Psychiatry, 2022)
Abstract Objective The majority of suicide decedents have had contact with health services in the months before their death. Contacts for mental health services present potential suicide prevention opportunities. This study aims to compare contact-based characteristics among those who did and did not die by suicide in the year subsequent to clinical mental health (MH) contact with the public health system in Victoria, Australia. Methods A population-based nested case-control study was carried out of those who had MH related hospital and community contacts with the public health system. Cases (those who died by suicide) were matched to controls (those who didn’t) by age and sex. These data were linked with records of suicide that occurred in the 12 months following the health service contact. Victorian residents 10 years of age and older at the time of contact (contacts between 01 January 2011 and 31 December 2016 (483,933 clients)) were selected. Conditional logistic regression models were used to assesses the association between contact-based characteristics and suicide in the study population. Results There were 1,091 suicide decedents who had at least one MH contact with the public health system in the 12 months prior to the suicide during the six-year period. Overall, controls used more MH services than cases; however, proximal to the event, cases showed an increased use of MH services. The association between type of service and suicide varied by service type: hospital admissions and emergency department presentations showed a positive association with suicide (OR>1), and the association increased as the event got closer, while residential stays and community contacts showed a negative association (OR<1), however, increased in magnitude as the event got closer (OR~1). Conclusions Suicide decedents had less contact with MH services than non-decedents; however, evidence suggests suicide decedents reach out to MH services proximal to suicide. An increase in MH service contact by an individual could be an indication of suicide risk and therefore an opportunity for intervention. Further, community level contact should be further explored as a possible prevention mechanism considering the majority of suicide decedents do not access the public clinical MH services.